Former les enseignants à l’analyse didactique. Un cas en histoire - Sylvain Doussot (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The article analyzes the case of a student in a master's degree program in history teacher training in a training-through-research program that leads her to learn the concepts of history didactics. This case is worth mentioning because of its exceptionality, which allows us to draw the conditions for this learning through a "training didactics" approach (to the didactics of history) which puts in problematic relation the didactic system: the knowledge aimed at (didactic concepts), the knowledge brought into play by the student and the knowledge brought into play by the training system. The path and the traces of the path of this student provide indeed rare data of a qualitative analysis of a professional and academic training through research. From the theoretical angle of learning by problem construction and working on epistemological obstacles, we compare the data (successive writings of the student, transcripts of exchanges in seminars and interviews, email exchanges over the course of the year) and our didactic hypotheses (the obstacle constituted for students by the apprehension of teaching situations separating the functioning of disciplinary knowledge and pedagogical relations). It emerges from the analysis that the main condition for the learning observed in the appropriation of concepts by this student consists of a process of continuous comparison, in the sense of Grounded Theory (Glaser and Strauss, 1967), framed by the action of the trainer. This opens up perspectives concerning training through research.